2016
DOI: 10.1128/aac.00198-16
|View full text |Cite
|
Sign up to set email alerts
|

Study of Two Separate Types of Macrolide-Resistant Mycoplasma pneumoniae Outbreaks

Abstract: bTo study the complete natural process of a Mycoplasma pneumoniae outbreak in a semiclosed room such as a primary school room, we investigated two separate M. pneumoniae outbreaks involving 81 students in total in two primary schools in Hangzhou, China. M. pneumoniae isolates from pharyngeal swabs were detected by fluorescence quantitative real-time PCR (RT-PCR) and culture. The class in school M had 39 students, with 12 (30.8%) with positive M. pneumoniae detection results. The class from school J had 42 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Subsequently, cases began to appear in the neighboring class. This result was different from previous research result of outbreaks in two primary schools [19]. This result indicates that good environmental and hygienic conditions are important for the prevention and control of respiratory infections disease outbreaks.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Subsequently, cases began to appear in the neighboring class. This result was different from previous research result of outbreaks in two primary schools [19]. This result indicates that good environmental and hygienic conditions are important for the prevention and control of respiratory infections disease outbreaks.…”
Section: Discussioncontrasting
confidence: 96%
“…Zheng et al reported that the MRMP rates increased from 17% in 2005 to 76% in 2006 and 100% in 2007 and 2008 in Shanghai, China [11]. Wang et al reported that the MRMP was at a high rate of more than 90% from 2008 to 2012 in Beijing [19]. The above research results showed that MRMP spread rapidly in parts of Asia.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In South Africa, Carrim et al ( 10 ) found age under 6 years to be an independent risk factor for severe disease (odds ratio, 7.1; 95% CI, 1.7–28.7). High levels of macrolide resistance have been noted in Japan (50–90%) ( 11 ) and China (90–100%) ( 12 , 13 ). Routine macrolide resistance monitoring was not systematically in Europe and the United States, which may contribute to the under-detection of macrolide-resistant MP or reflect low levels of macrolide resistance reported ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%